Different Chilling-Induced Symptoms and the Underlying Oxidative Stress and Antioxidative Defense in the Exocarp and Mesocarp of Immature Sponge Gourd (Luffa cylindrica) Fruit - Chuenchom, Pichaya; Noichinda, Sompoch; Bodhipadma, Kitti; Wongs-Aree, Chalermchai; Leung, David W. M. (Applied Science and Engineering Progress, 2021)
Immature sponge gourd fruit is consumed as a vegetable with a limited shelf life. Although cold storage is a simple and powerful tool for maintaining postharvest fruit quality, storage at a low temperature may not be appropriate for vegetables as some chilling injury (CI) of the immature sponge gourd fruit may occur. Therefore, this research aimed to elucidate the relationship between CI, oxidative stress, and the antioxidative defense mechanisms in the exocarp and mesocarp of immature sponge gourd fruit. After storage at 5°C for 6 days, visual CI symptoms, including browning and surface pitting, were found in the peel (exocarp) but not in the mesocarp. There were, however, more dead cells (stained by Evans blue) in the mesocarp of the fruit stored at 5°C. There was a more considerable increase in the electrolyte leakage rate in both fruit tissues held at 5°C than 25°C. The CI was correlated with malondialdehyde (MDA) levels in the tissues. The MDA of fruit exocarp at 5°C was 1.6 fold higher than that at 25°C on day 6, while the lipoxygenase (LOX) activity in mesocarp was 50% higher in fruit stored at a lower temperature. The action of ascorbate peroxidase (APX) was high in the exocarp of the fruit stored at 5°C, but there appeared to be a continuous depletion of the co-substrate or ascorbic acid. In conclusion, the CI in the exocarp was mainly associated with a high level of reactive oxygen species (ROS). In contrast, the CI in the mesocarp appeared to be primarily associated with increased lipid peroxidation by the elevated LOX activity under cold stress compared to storage at 25°C.